The Use of Digital Marketing and Its Impact on Increasing MSME Sales - Khaerani, Siti Nurul; Sudarmiatin, Sudarmiatin (International Journal Labs, 2022)
The increasing number of internet users provides opportunities for MSMEs to use digital marketing as one of their marketing strategies. There are several digital marketing platforms that can be used, including the Web, SEO, Social Media and others. This article discusses the use of digital marketing for MSMEs and the impact of using digital marketing on increasing MSME sales. The research method used is qualitative research. With the number of informants as many as 12 MSME owners who were interviewed with different types of businesses. The results show that social media is one of the most widely used digital platforms by MSMEs. And give the impact of an increase in sales of SMEs. In some MSMEs the increase in sales through online is no more than traditional sales.